2011
DOI: 10.1007/s10856-011-4439-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone substitute biomedical material of multi-(amino acid) copolymer: in vitro degradation and biocompatibility

Abstract: Degradable polymers with good mechanical strength as bone repair biomaterials have been paid more attention in biomedical application. In this study, a multi-(amino acid) copolymer consisting of 6-aminocaproic acid and five natural amino acids was prepared by a reaction of acid-catalyzed condensation. The results revealed that the copolymer could be slowly degradable in Tris-HCl solution, and lost its initial weight of 31.9 wt% after immersion for 12 weeks, and the changes of pH value of Tris-HCl solution were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…This copolymer could be degraded in HCL-Tris solution with weight loss of about 30 wt% after 12 weeks of soaking. 16 In particular, our results show that during the degradation period, this copolymer had no significant effect on the pH of the ambient environment and maintained a complete structure and adequate mechanical strength compared with other degradation polymers, such as polylactic acid and it copolymers. Cell culture experiments and in vivo implantation results show that the copolymer also had good biocompatibility.…”
Section: Introductionmentioning
confidence: 67%
“…This copolymer could be degraded in HCL-Tris solution with weight loss of about 30 wt% after 12 weeks of soaking. 16 In particular, our results show that during the degradation period, this copolymer had no significant effect on the pH of the ambient environment and maintained a complete structure and adequate mechanical strength compared with other degradation polymers, such as polylactic acid and it copolymers. Cell culture experiments and in vivo implantation results show that the copolymer also had good biocompatibility.…”
Section: Introductionmentioning
confidence: 67%
“…11,12 The MAC that is composed of 6-aminocaproic acid and five amino acids exhibits good ductility and biocompatibility. 13 Our previous works have suggested that the amide-calcium-amide linkage and hydrogen bond formed between n-CDHA and MAC endow this biocomposite with eligible mechanical strength (compressive strength in the range of 88-129 MPa), degradability, cytocompatibility, and osteoconductivity. [10][11][12][13] However, the n-CDHA/MAC composite material has relatively poor flexibility, which limits its application in repairing complex and irregular bone defects.…”
Section: Introductionmentioning
confidence: 94%
“…24,25 The PAA copolymer could be degraded in HCL-Tris solution with weight loss of ~30 wt% after 12 weeks of soaking, and it had no significant effect on the pH value of the ambient environment during the degradation period. 26 If the pH value in the ambient solution was decreased, it was believed to induce the inflammatory reaction in vivo. 27 Cell culture experiments and in vivo implantation results showed that the PAA also had good biocompatibility.…”
mentioning
confidence: 99%
“…27 Cell culture experiments and in vivo implantation results showed that the PAA also had good biocompatibility. 26 When implanted in cortical bone of the dogs, the PAA copolymer implants were directly connected with the host bone tissue without obvious intervening connective layer, and some new bone tissues were found to extend along the copolymer surface, which was known as bone-bonding. 26 Bone-bonding could ensure that the implant integrated with natural bone through biochemical reaction at the interface between biomaterials and bone tissue, which was in favor of implant fixation in host bone.…”
mentioning
confidence: 99%
See 1 more Smart Citation